Inovasi Perpustakaan Perguruan Tinggi Muhammadiyah–‘Aisyiyah (PTMA) Menghadapi Pandemi Covid-19: Sebuah Studi Literatur Bunga Rampai - Kusuma, Gretha Prestisia Rahmadian (Daluang: Journal of Library and Information Science, 2021)
Introduction. The COVID-19 pandemic has had an impact on education systems around the world, including Indonesia. The government carried out temporary closure of public services to reduce the number of additional cases. One of the community services affected is the library as a support for education. As a supporter of education, the perceived impact is the non-utilization of services in the library. Efforts made by the library to continue to provide services are by changing the system and management mechanism in the library. This paper aims to find out the innovations and strategies implemented in several PTMA libraries in the era of the Covid-19 pandemic.Methodology. This study uses a literature review to collect data and documentation to support the analysis.Result. The result of this paper is that PTMA library librarians must be able to use facilities or technology to serve the academic community.Conclusion. The COVID-19 pandemic has not only hurt society. The other side of the Covid-19 pandemic is being able to develop competence through online seminars. In addition, the handling of the COVID-19 pandemic, which is gradually improving, has forced libraries to reopen services while still implementing health protocols to suppress the rate of transmission.